Legal Certainty and Justice in Palestinian Independence from the Perspective of the 1945 Constitution - Zikrullah, Zikrullah (Peradaban Journal of Law and Society, 2024)
This article aims to analyze the legal certainty regarding the future of Palestinian independence from the perspective of the 1945 Constitution. On the other hand, it also aims to analyze the legal justice concerning the future of Palestinian independence from the same perspective. This article employs qualitative research, conducting a historical study of the Palestine-Israel conflict phenomenon, using a normative approach. It provides legal certainty through the theory of legal norms proposed by Gustav Radbruch, where moral norms can meet the demands of legal reality. Currently, there is no legal certainty for the Palestinian people, resulting in continued occupation and increased casualties. Legal justice for the Palestinian people cannot be felt due to the lack of legal standing, which hinders the realization of justice. The first paragraph of the Preamble to the 1945 Constitution implies that independence is the right of all nations and rejects all forms of colonialism and oppression. Therefore, based on this principle, Palestine must assert its independence, as it has been colonized and oppressed by Israel. Artikel ini bertujuan untuk menganalisis kepastian hukum mengenai masa depan kemerdekaan Palestina dari perspektif Konstitusi 1945. Di sisi lain, artikel ini juga bertujuan untuk menganalisis keadilan hukum sehubungan dengan masa depan kemerdekaan Palestina dari perspektif yang sama. Artikel ini menggunakan penelitian kualitatif dengan melakukan studi historis fenomena konflik Palestina-Israel, dengan pendekatan normatif. Artikel ini menyediakan kepastian hukum melalui teori norma hukum yang diajukan oleh Gustav Radbruch, di mana norma moral dapat memenuhi tuntutan realitas hukum. Saat ini, tidak ada kepastian hukum bagi rakyat Palestina, yang mengakibatkan terus berlanjutnya pendudukan dan peningkatan korban. Keadilan hukum bagi rakyat Palestina tidak dapat dirasakan karena kurangnya status hukum, yang menghambat terwujudnya keadilan. Paragraf pertama Pembukaan UUD 1945 menyiratkan bahwa kemerdekaan adalah hak semua bangsa dan menolak segala bentuk kolonialisme dan penindasan. Oleh karena itu, berdasarkan prinsip ini, Palestina harus menegakkan kemerdekaannya, karena telah dijajah dan ditindas oleh Israel.